Re-Migration Decision Making: An Analysis of Push and Pull Factors Influencing People's Decision to Return to High Disaster Risk Areas - Azura Calista Shafa Kamila; I Dewa Made Frendika Septanaya (Jurnal Penataan Ruang, 2025)
The provision of post-disaster relocation programs aims to provide adequate shelter and ensure the safety of the community. In Lumajang, after eruption of Mount Semeru, many disaster-affected residents chose to return to their areas despite the high risks involved. Those who returned assumed that the government's relocation had not fully met their expectations and had an impact on various aspects. In addition, emotional attachments are one of the reasons for the return of the community. This shows that there are complex factors between push and pull that influence their decision to return to high disaster risk area. Using the push-pull migration framework, this study aims to analyze the factors that influence people's decision to return to their area of origin post-eruption of Mount Semeru. In this study, push factors are analyzed through housing satisfaction, while pull factors are analyzed through place attachment and risk perception. The analysis method used is descriptive statistical analysis. The results show that the factors encourage people to return to area of origin are caused by several things such as proximity to work locations (3.57), availability of integrated livestock (3.46), and availability of home utilities (3.45). Meanwhile, the pull factors that influence people's decisions are employment opportunities (3.45), availability of income sources (3.44), biodiversity of biological resources (3.43), and limited disaster information (3.35). In general, the high mean value of these indicators has the potential to encourage reluctance to stay in the new relocation location and become one of the reasons for people to consider returning to their home areas that have a higher level of disaster risk.